It’s a Man’s World: Does Orthotopic Liver Transplantation in the Elderly Male Confer an Additional Risk on Survival? - Eoin Slattery; John E Hegarty; P Aiden McCormick (Canadian Journal of Gastroenterology)
BACKGROUND: Orthotopic liver transplantation (OLT) in a well-selected population is a highly successful procedure, with one-year survival rates reported to be as high as 90%. Advanced age is considered to be a contraindication. Survival rates in patients >60 years of age appear to be comparable with those of younger patients. However, little objective data exist on the outcomes of patients >65 years of age undergoing OLT.